Radiation effect on the performance of robot manipulator. (2017) - Li, Shimeng; Wang, Hongfei; Zheng, Yuan F.; Cao, Lei (Raymond)
Robots have great potential in substituting human beings for operations in accidents of nuclear power plants; however, knowing that the radiation will potentially damage the robot components, how the robot will perform in radiation environment has never been discussed. In this paper, we claim that the performance of robot manipulators will vary because servo motor will degrade due to the radiation. Degrading to the motor occurs because radiation damages the magnets residing inside the motor. Once damage is done, the degrading of the motor is permanent in a deterministic way, which is reflected in the reduced back electromotive force (back-emf). We first use MATLAB to simulate the performance of servo motor variation before and after radiation based on the model of radiation demagnetisation, and then build a three degree-of-freedom (DOF) manipulator to analyse the motion variation of a robot arm based on the results of motor performance variation.